2009
DOI: 10.1016/j.jconrel.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effective GDNF brain delivery using microspheres—A promising strategy for Parkinson's disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) has shown promise in the treatment of neurodegenerative disorders of basal ganglia origin such us Parkinson's disease (PD). In this study, we investigated the neurorestorative effect of controlled GDNF delivery using biodegradable microspheres in an animal model with partial dopaminergic lesion. Microspheres were loaded with N-glycosylated recombinant GDNF and prepared using the Total Recirculation One-Machine System (TROMS). GDNF-loaded microparticles were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 27 publications
3
97
1
Order By: Relevance
“…Equally, it is generally accepted that successful translation of GDNF to clinical practice will first require resolving the crucial delivery issues posed by NF. Different strategies including direct gene transfer using recombinant virus (For review see [12]) and polymeric MP has been proposed to improve protein delivery to the brain [11,36]. All research using GDNF-PLGA-MP in rat PD models reported animal functional recovery together with increase in striatal DArgic innervation [36,37].…”
Section: Dds For Neurotrophic Factor Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, it is generally accepted that successful translation of GDNF to clinical practice will first require resolving the crucial delivery issues posed by NF. Different strategies including direct gene transfer using recombinant virus (For review see [12]) and polymeric MP has been proposed to improve protein delivery to the brain [11,36]. All research using GDNF-PLGA-MP in rat PD models reported animal functional recovery together with increase in striatal DArgic innervation [36,37].…”
Section: Dds For Neurotrophic Factor Deliverymentioning
confidence: 99%
“…Different strategies including direct gene transfer using recombinant virus (For review see [12]) and polymeric MP has been proposed to improve protein delivery to the brain [11,36]. All research using GDNF-PLGA-MP in rat PD models reported animal functional recovery together with increase in striatal DArgic innervation [36,37]. In the next step, our recent studies evaluating GDNF-MP efficacy in a primate PD model demonstrated that long-term controlled brain delivery of microencapsulated GDNF induced functional and structural recovery of the dopaminergic nigrostriatal pathway (Unpublished results).…”
Section: Dds For Neurotrophic Factor Deliverymentioning
confidence: 99%
“…27 In particular, the efficacy of NTFs such as GDNF, or angiogenic factors like VEGF, in the upregulation of essential neurogenic processes makes them ideal candidates for modifying the evolution of this disorder. 4,5,28 Previous studies published by our group, as well as research conducted by numerous other laboratories, 16,29,30 has demonstrated that the administration of VEGF or GDNF improves behavioral deficits as well as decreases neuronal degeneration in different animal models of neurodegenerative disorders. 7,11,20 Nevertheless, the essential problems for the application of these hydrophilic molecules are their short half-life and rapid degradation rate in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…The failure brought some doubt about trophic factor delivery for PD treatment. Different strategies including direct gene transfer using recombinant adeno-associated virus and PLGA microparticles were proposed to improve brain GDNF delivery [39][40][41][42][43][44].…”
Section: Microparticles For Neurotrophic Factor Deliverymentioning
confidence: 99%
“…All the studies using GDNF-PLGA microspheres reported an animal functional recovery together with an increase in dopaminergic innervation in the striatum due to the sprouting of the fibers spared by the lesion. Moreover, none of the animals that received the glycosylated protein developed antibodies against GDNF demonstrating the safety of glycosylated GDNF use [41].…”
Section: Microparticles For Neurotrophic Factor Deliverymentioning
confidence: 99%